Use of tidal breathing curves for evaluating expiratory airway obstruction in infants. (2nd December 2018) - Hevroni, Avigdor; Goldman, Aliza; Blank-Brachfeld, Miriam; Abu Ahmad, Wiessam; Ben-Dov, Lior; Springer, Chaim
ABSTRACT: Objective : To evaluate tidal breathing (TB) flow-volume and flow-time curves for identification of expiratory airway obstruction in infants. Methods : Pulmonary function tests were analyzed retrospectively in 156 infants aged 3–24 months with persistent or recurrent respiratory complaints. Parameters derived from TB curves were compared to maximal expiratory flow at functional residual capacity (V ˙ maxFRC) measured by rapid thoracoabdominal compression technique. Analyzed parameters were: inspiratory time (tI ), expiratory time (tE ), tidal volume, peak tidal expiratory flow (PTEF), time to peak tidal expiratory flow (tPTEF ), expiratory flow when 50% and 25% of tidal volume remains in the lungs (FEF50, FEF25, respectively), and the ratios tPTEF /tE, tI /tE, FEF50 /PTEF, and FEF25 /PTEF. Statistical comparisons between flow indices and TB parameters were performed using mean squared error and Pearson's sample correlation coefficient. The study population was also divided into two groups based on severity of expiratory obstruction (above or below z-score forV ˙ maxFRC of −2) to generate receiver operating characteristic (ROC) curves and calculate discriminatory values between the groups. Results : TB parameters that were best correlated toV ˙ maxFRC were: tPTEF /tE, FEF50 /PTEF, and FEF25 /PTEF, with r = 0.61, 0.67, 0.65, respectively ( p < 0.0001 for all). ROC curves for FEF50 /PTEF, FEF25 /PTEF and tPTEF /tE showed areas under the curve of 0.813, 0.797, and 0.796, respectively. Cutoff value z-scores of −0.35, −0.34, and −0.43 for these three parameters, respectively, showed an 86% negative predictive value for severe airway obstructions. Conclusion : TB curves can assist in ruling out severe expiratory airway obstruction in infants.